2004
DOI: 10.1023/b:agfo.0000013269.19284.53
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrient concentration of two native forage legumes inoculated with Rhizobium and Mycorrhiza in Missouri, USA

Abstract: The Center for Agroforestry at the University of Missouri has tested numerous native legumes for potential use in agroforestry and selected Illinois bundleflower ͑Desmanthus illinoensis ͑Michaux͒ MacMillan ex Robinson and Fern.͒ and panicled tick clover ͑Desmodium paniculatum ͑L.͒ DC.͒ for further testing. Our objective was to document the effect of arbuscular mycorrhizae ͑AM͒ ͑Glomus spp.͒ and Rhizobium on growth and nutrient concentration of these legumes. Seeds were planted in a greenhouse and inoculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This result indicated the synergistic effect between AMF and Rh on the symbiotic association of white clover. AMF has no strict compatibility with host plants, whereas the symbiotic system of legume-AMF-Rh has obviously mutual selectivity (Shockley et al 2004). The positive Plant, Soil and Environment, 66, 2020 (6) (Maillet et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This result indicated the synergistic effect between AMF and Rh on the symbiotic association of white clover. AMF has no strict compatibility with host plants, whereas the symbiotic system of legume-AMF-Rh has obviously mutual selectivity (Shockley et al 2004). The positive Plant, Soil and Environment, 66, 2020 (6) (Maillet et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Total biomass (roots + shoots) was used as a measure of plant growth response to AM fungi in most of the studies but in one study, total biomass was calculated as the sum of leaf dry mass (g), stem dry mass (g), and root fresh mass (g) (Shockley et al. ). When data for more than one experiment were presented in the same paper (e.g., Klironomos ), the experiments were analyzed separately (i.e., considered independent) in the meta‐analysis (Data ).…”
Section: Methodsmentioning
confidence: 99%
“…The increase of the availability of elements specially, calcium which plays the main role in cell signaling which could lead to switch on or accelerate the function of several genes such as protein kinases and other genes related with photosynthesis and eventially, affect the plant growth. Inoculation with mycorrhiza increased all plant growth variables such as number of leaves, stem fresh and dry weights and root dry weight Shockley et al (2004). Gahoonia and Nielsen (2004) reported that the inoculation with mycorrhiza enhanced the release of organic acids and higher acid phosphatase activity in the rhizosphere which may be useful for increasing phosphorus acquisition from inorganic and organic phosphorus pools to the plant.…”
Section: Department Ofmentioning
confidence: 99%